The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.36371/port.2022.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Loss of a Family Member and Oral Lichen Planus in Iraqi Population

Abstract: background Oral lichen planus is common oral mucosal lesions with several predisposing factors, but with poorly identified etiology. Stressor factors could be one of etiological causes for eruption of the lesion and/or a predisposing factor for its appearance, aggravating the excited lesion. The aim of this study to evaluate certain circumstances that were passed on Iraqi population that may be related to elevated OLP incidence in Iraq. Material and method One hundred twenty-nine clinical charts for oral liche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Before and after treatment, the salivary levels of interleukin-6 were assessed in each patient and the levels found to be higher after PRP treatment; Table (2). in relation to the location of the lesion, its size, the phenotype of the lesion, colour change, and signs or symptoms that the patient was experiencing the levels of IL-6 were compared.…”
Section: Interleukin-6 Level Before and After Prp Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before and after treatment, the salivary levels of interleukin-6 were assessed in each patient and the levels found to be higher after PRP treatment; Table (2). in relation to the location of the lesion, its size, the phenotype of the lesion, colour change, and signs or symptoms that the patient was experiencing the levels of IL-6 were compared.…”
Section: Interleukin-6 Level Before and After Prp Injectionsmentioning
confidence: 99%
“…Oral lichen planus (OLP) is a chronic inflammatory lesion of the oral mucosae, its related to aberrant cellular immunity (1), Genetics, psychological state and infectious agents may act as causes and /or triggers (2). It's found that all the possible causes of OLP lesion production have the capacity to modulate the oxidative status (3), and this is approved by the decreased salivary anti-oxidant capacity in OLP patients (4).…”
Section: Introductionmentioning
confidence: 99%
“…''An oral mucosal illness with an unknown cause called oral lichen planus (OLP) is a chronic inflammatory T-cell-mediated condition'' [3]''. ''Infectious agents, psychological conditions, and genetic factors can all operate as causes or triggers'' [4]''. ''It has been discovered that all potential causes of OLP lesion generation have the ability to alter the oxidative status'' [5],''and this is supported by the fact that OLP patients have lower salivary anti-oxidant capability'' [6]''.…”
Section: Introductionmentioning
confidence: 99%